Metabolic Analysis of Schizochytrium Mutants With High DHA Content Achieved With ARTP Mutagenesis Combined With Iodoacetic Acid and Dehydroepiandrosterone Screening - Zeng, Lei; Bi, Yanqi; Guo, Pengfei; Bi, Yali; Wang, Tiantian; Dong, Liang; Wang, Fangzhong; Chen, Lei; Zhang, Weiwen (Frontiers in Bioengineering and Biotechnology, 2021)
High DHA production cost caused by low DHA titer and productivity of the current Schizochytrium strains is a bottleneck for its application in competition with traditional fish-oil based approach. In this study, atmospheric and room-temperature plasma with iodoacetic acid and dehydroepiandrosterone screening led to three mutants, 6-8, 6-16 and 6-23 all with increased growth and DHA accumulations. A LC/MS metabolomic analysis revealed the increased metabolism in PPP and EMP as well as the decreased TCA cycle might be relevant to the increased growth and DHA biosynthesis in the mutants. Finally, the mutant 6-23, which achieved the highest growth and DHA accumulation among all mutants, was evaluated in a 5-L fermentor. The results showed that the DHA concentration and productivity in mutant 6-23 were 41.4 g/L and 430.7 mg/L/h in fermentation for 96 h, respectively, which is the highest reported so far in literature. The study provides a novel strain improvement strategy for DHA-producing Schizochytrium.